Analysis of Caffeine Content in Roasting Temperature Variation of Robusta Luwak Coffee from Garahan Jember Plantation using UV-Vis Spectrophotometry Method - Bowo Eko Cahyono; Winda Arif Febrayanti; Misto Misto (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
ABSTRACT- The increasing demand for high-quality coffee has led to making various tests to guarantee the quality of coffee to be accepted in the market. This study aimed to know the caffeine content in Robusta Luwak coffee roasted at different temperatures. The coffee used in this study is pure and mixed with rice. This study was conducted using various roasting temperatures, namely 190⁰C and 240⁰C. The additional material combined with the coffee is rice with mass fractions of 10%, 20%, 30%, 40%, and 50%. The absorbance value of caffeine in the sample is measured in the wavelength of the maximum absorbance of pure caffeine solution, 273 nm. The results showed that pure Robusta Luwak coffee with roasting temperatures of 190⁰C and 240⁰C had caffeine content of 1.10% and 0.94%, respectively. In mixed Robusta Luwak coffee, the highest caffeine content was at 190⁰C with a caffeine content of 0.89% in the composite material mass fraction of 10%, and the lowest caffeine content was at 240˚C with a mass fraction of 50% mixed material that had a caffeine content of 0.31%. In the serving dose, those two samples showed that the caffeine content was laid in the safe interval according to SNI and FDA standards.KEYWORDS: caffeine; robusta Luwak coffee; temperature; wavelength.